2022
DOI: 10.1155/2022/9464312
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Concentration Improves the Quality and Antioxidant Capacity of Pear Paste

Abstract: A vacuum concentration method was established to produce pear paste using fresh pear juice in this study. The optimal condition was determined by comparing the quality indexes, contents of total phenol and flavonoid, and antioxidant properties of the pear paste produced by traditional heating concentration and vacuum concentration. Electronic nose and electronic tongue were introduced in this study to provide digital smell and taste indicators. The results showed that the best vacuum concentration temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Although the water was able to elute some of the sugars, the methanol eluate still contained a significant amount of sugars and pigments. These water‐soluble pigments are produced by the Maillard reaction during the production of pear paste 37 . Water‐soluble pigments cannot be absorbed by graphitized carbon black.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the water was able to elute some of the sugars, the methanol eluate still contained a significant amount of sugars and pigments. These water‐soluble pigments are produced by the Maillard reaction during the production of pear paste 37 . Water‐soluble pigments cannot be absorbed by graphitized carbon black.…”
Section: Resultsmentioning
confidence: 99%
“…These water-soluble pigments are produced by the Maillard reaction during the production of pear paste. 37 Water-soluble pigments cannot be absorbed by graphitized carbon black. To minimize the interference of sugars and pigments on the assay, an attempt was made to dissolve the pear paste into water and extract the target with acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum-concentrated beetroot juice at 50 and 55 °C increased DPPH inhibition by 18% but remained unchanged when the temperature increased to 60 °C [14]. Similarly, Li, et al [13] found that vacuum-concentrated pear paste increased in DPPH scavenging with the applied temperature in the range of 55 and 60 °C, then gradually decreased when the temperature increased from 65 to 75 °C. The changes in antioxidant ability would involve the cumulative of potentially anti-oxidative components in the juices.…”
Section: Changes In Dpph Scavenging Capacity Of Lime Juices During Va...mentioning
confidence: 89%
“…Freeze-concentrated juices were 15.67% higher in DPPH inhibition compared to vacuum-concentrated juices (t(11) = 19.3012, p < 0.0001). Freeze concentration caused an increase in the anti-oxidative activity of various concentrated products such as apple [20], blueberry [63], and orange [21] juices, as well as pear paste [13]. The increase in the DPPH scavenging activity would be contributed by a great improvement in anti-oxidative components such as ascorbic acid, TPC, and flavonoids found in freeze-concentrated lime juices.…”
Section: Changes In Dpph Scavenging Capacity Of Lime Juices During Va...mentioning
confidence: 99%
See 1 more Smart Citation